Kewenangan Mahkamah Agung dalam Proses Penyelesaian Sengketa Perbuatan Melanggar Hukum pada Tingkat Kasasi - Raffael Moreno Chrishans; Darell Tri Jaya; Rasji Rasji (Publikasi Indonesia, 2022)
When there is a dispute regarding the authority to adjudicate between one court environment and another court environment, then in the end the Mahkamah Agung (MA) as the highest court will use its power to try and resolve the dispute at the Cassation level or at the Judicial Review (PK) level, with Thus, if disputes over the jurisdiction of adjudicators continue to be submitted to the Supreme Court of Justice by the litigants, then the accumulation of cases at the Mahkamah Agung (MA) as the court of final instance in relation to these disputes cannot be avoided. The research methodology at this writing is to use juridical research (legal research) is a form of scientific activity in the field of law which uses methods, systematics and a thinking that is specific to studying laws, using certain analysis. The purpose of this paper is: 1) to find out what are the main duties and functions of the Supreme Court. 2) to find out what judicial power is, 3) to know the authority of the Mahkamah Agung in the settlement of unlawful acts disputes at the cassation level.